PROTOTIF ALAT PENYANGRAI KOPI TIPE ROTARI DILENGKAPI PRE-HEATER - Rusnadi, Irawan (KINETIKA, 2018)
Coffee is one of the most popular and the most consumed because the taste it has. Roasting is an important step in the flavor development and aroma of coffee beans. Roasting is a way of drying using high temperature. High temperatures are able to change the chemical components and physical structure of a material. The materials used in this research are robusta coffee beans. The roasted coffee beans used a rotary roaster drum. Heating system using direct heating. The parameters of roasting results include moisture content, energy requirements during the process roasting, fuel consumption and roasting efficiency . The roasting machine is equipped with a cooling bin of the post-roasting coffee bean with a blower system with the working principle of blowing hot air into the environment resulting in cooling process. The results of the study revealed that the lowest moisture content and highest energy requirements were obtained at a temperature of 200oC which was 0.60% with an energy requirement of 605.09 kJ and the highest efficiency was obtained at a temperature of 180oC at 8 minutes which is 33.43%.